Análisis de la cartera de crédito del Supermercado Dismero S.A a pequeños negocios - Tomalá Rodríguez, Lisset Margarita (2019)
The company DISMERO SA began its economic activities from the year 1996 with the modality of wholesale stores of groceries to popular sectors in the provinces of Los Ríos and Guayas, in 1998 they opened a store in the city of Babahoyo with the name of “ Commercial Medina ”. From that time until 2002, their sales evolved significantly, which led them to be renamed “Comercial Medina Hnos.” Until 2005 where they were established as the Company DISMERO S.A. The company DISMERO S.A is a supermarket dedicated to the sale of groceries, through its self-service stores, in which a differentiated service is offered to the other supermarkets. This is how DISMERO S.A, clearly observing its economic growth due to the increase in its sales, entered into new methods